Novel thermal energy recovery system testing. (February 2019) - Royale, Andrew; Simic, Milan; Lappas, Petros; Schiffer, Philipp; Palaniswamy, Ramchandran
Abstract: Thermal energy recovery systems, based on thermoelectric generator (TEG) units, used in the internal combustion engine (ICE) vehicles, enable recovery of wasted heat energy, generated from the combustion process by converting it into electrical energy. Recovery systems are placed into the exhaust subsystems, just before and after the catalytic converters, where temperatures range is from 200 °C to 400 °C. This modest arrangement is a result of TEG units working temperatures and limitations. In the early stages TEG units were placed into the exhaust mufflers where the temperatures are around 200 °C. This paper is a report on the green transportation project that carries on from the previous research, testing and validation conducted in the School of Engineering. We investigated process where, the exhaust port of the engine cylinder head was identified as an optimal location to place the latest technology, high temperature, TEG units. Maximum working temperature of these new devices is 850 °C so that it is safe to place them into the exhaust port of the cylinder head, where the temperatures are around 800 °C.